A Case Study for Using the Quality Function Deployment Method as a Quality Improvement Tool in the Universities - Kelesbayev, Dinmukhamed; Kalykulov, Kuatbek; Yertayev, Yermek; Turlybekova, Altynay; Kamalov, Akhmet (International Review of Management and Marketing, 2016)
In a global scope, many countries give big efforts to capture universal specifications by strengthening their cooperations in the field of education with other countries in order to develop a global position on the international level just like in many areas. However, it is considered that raising the quality of education at the international level of these countries are known to be a long way they should take. Therefore, in this study, the Quality Function Deployment as a systematic quality improvement tool addressing the education system in its entirety is discussed and it is intended to contribute to improving the quality of education in terms of its importance to countries. This study is based on the demands of the course students carried out at universities and reveals the quality of the education services. According to this target, the Quality Function Deployment method is utilized to determine whether there is an education service pointed out by the needs and expectations of students or not and also the policies that should be followed by the universities is discussed. Keywords: Education Quality, Quality Function Deployment, Universities. JEL Classifications: I21, I23